(untitled) (Eurasian Journal of Ecology, 2025)
Under the sharply continental climate of Astana, the selection of resilient ornamental shrub species is especially important for establishing durable and sustainable urban green infrastructure. The aim of this study was to assess the survival and adaptation characteristics of ornamental flowering shrubs in urbanized areas of the capital of Kazakhstan. The analysis was carried out on several experimental plots that differed in agrochemical soil properties, including nutrient availability, humus content, and acidity. The results showed an average plant loss rate of 28.6%. Glossy cotoneaster (Cotoneaster lucidus) demonstrated thаe highest resilience, with losses below 1%, while common ninebark (Physocarpus opulifolius) exhibited moderate tolerance, with losses ranging from 15% to 25%. Panicle hydrangea (Hydrangea paniculata) was identified as the least adapted species, with mortality reaching 24.4%. Plant survival was strongly influenced by soil potassium and phosphorus levels, organic matter content, and pH balance. Based on these findings, it is recommended to prioritize glossy cotoneaster and common ninebark for urban landscaping projects in Astana, whereas panicle hydrangea should be used only in areas with favorable agrochemical conditions. Future research should focus on identifying and testing new drought- and cold-tolerant cultivars to further enhance the sustainability of Astana’s urban green spaces. Keywords: ornamental shrubs; urban ecology; Astana; plant adaptation; landscaping.